2019
DOI: 10.3390/molecules24173021
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Petroleum Hydrocarbons by Bacillus subtilis BL-27, a Strain with Weak Hydrophobicity

Abstract: The biodegradation of petroleum hydrocarbons has many potential applications and has attracted much attention recently. The hydrocarbon-degrading bacterium BL-27 was isolated from petroleum-polluted soil and was compounded with surfactants to improve biodegradation. Its 16S rDNA and rpoD gene sequences indicated that it was a strain of Bacillus subtilis. Strain BL-27 had extensive adaptability and degradability within a broad range of temperatures (25–50 °C), pH (4.0–10.0) and salinity (0–50 g/L NaCl). Under o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(22 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…All supernatants from the three cycles of extraction were filtered and mixed, and petroleum ether was added to make a final extractant solution of 40 ml. The filtrate was diluted, and the diesel oil concentration in the dilute was determined by absorbance reading in UV spectrophotometer at 225 nm (Lu et al, 2011;Wang et al, 2019a;Zheng et al, 2019). Then the concentration of diesel was determined from the regression equation prepared from calibration of a known concentration and absorbance.…”
Section: Diesel Extraction and Analysismentioning
confidence: 99%
“…All supernatants from the three cycles of extraction were filtered and mixed, and petroleum ether was added to make a final extractant solution of 40 ml. The filtrate was diluted, and the diesel oil concentration in the dilute was determined by absorbance reading in UV spectrophotometer at 225 nm (Lu et al, 2011;Wang et al, 2019a;Zheng et al, 2019). Then the concentration of diesel was determined from the regression equation prepared from calibration of a known concentration and absorbance.…”
Section: Diesel Extraction and Analysismentioning
confidence: 99%
“…Earlier studies have also been reported degradation of various xenobiotic compounds and heavy metals by the members of genus Bacillus (Birolli et al, 2016 ; Upadhyay et al, 2017 ; Arora et al, 2018 ; Díez-Méndez et al, 2019 ). Wang et al ( 2019 ) reported the efficient biodegradation of petroleum hydrocarbons by B. subtilis BL-27. Viesser et al ( 2020 ) isolated new petroleum-degrading strains of B. thuringiensis and B. subtilis from the rhizosphere of Panicum aquaticum .…”
Section: Introductionmentioning
confidence: 99%
“…Bioremediation has been reported as an efficient method for the remediation of organic pollutants such as hydrocarbons [170][171][172], pesticides [66,173,174], polychlorinated biphenyls [175] and pharmaceuticals [176,177]. This technology is based on three strategies: biostimulation, bioaugmentation or a combination of both.…”
Section: Bioremediation Processes As a New Remediation Technologymentioning
confidence: 99%